2019
DOI: 10.4274/tjh.galenos.2019.2019.0079
|View full text |Cite
|
Sign up to set email alerts
|

Certain Killer immunoglobulin like receptor (KIR)/ KIR HLA class I ligand genotypes influence NK antitumor activity in acute myelogenous leukemia but not in acute lymphoblastic leukemia. A case control leukemia association study

Abstract: Objective:Natural killers (NK) cell function is mainly controlled by the expression of killer immunoglobulin-like receptors (KIRs) and their ligation with the corresponding ligands. The objective of this study was to investigate the putative association of KIRs, HLA class I ligands, and KIR/ligand combinations with rates of development of acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), and chronic myeloid leukemia (CML).Materials and Methods:The KIR/HLA I genotypes of 82 patients with leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
10
2
Order By: Relevance
“…Shahsavar et al reported a non‐significant increase in the frequency of the KIR3DS1 gene and a significantly reduced frequency of the KIR2DS3 gene in patients with AML compared to controls at Shariati Hospital, Tehran, Iran—a referral centre that admits patients from all over the country (Shahsavar et al., 2010). In contrast to our results, a lower frequency of KIR3DS1 was previously reported in Bulgarian patients with AML by Varbanova et al (Varbanova et al., 2019). In data reported by Vejbaesya et al, no significant difference in KIR gene distribution was found between Thai patients with AML and controls (Vejbaesya, Sae‐Tam, Khuhapinant, & Srinak, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Shahsavar et al reported a non‐significant increase in the frequency of the KIR3DS1 gene and a significantly reduced frequency of the KIR2DS3 gene in patients with AML compared to controls at Shariati Hospital, Tehran, Iran—a referral centre that admits patients from all over the country (Shahsavar et al., 2010). In contrast to our results, a lower frequency of KIR3DS1 was previously reported in Bulgarian patients with AML by Varbanova et al (Varbanova et al., 2019). In data reported by Vejbaesya et al, no significant difference in KIR gene distribution was found between Thai patients with AML and controls (Vejbaesya, Sae‐Tam, Khuhapinant, & Srinak, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…There are just a few studies about the association of KIR genes with AML as Shahsavar et al reported negative associations between KIR2DS3 and KIR3DS1 with AML in Iranian patients (Shahsavar et al., 2010) and Varbanova et al found negative association of KIR2DL5a and positive association of KIR2DS4fl with AML in Bulgarians (Varbanova, Mihailova, Naumova, & Mihaylova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The role of KIR2DL5 gene and its allelic variants for NK activity regulation is supported by the finding of other researchers as Shah-Hosseini et al 16 who demonstrated a higher frequency of KIR2DL5A allele in HBV recovered individuals compared to controls. The higher distribution of inhibitory KIR3DL1*004 observed by us in chronic HBV carriers may suggest increased NK-cell inhibition in chronic disease, although some data demonstrate lack of expression of the encoded receptor 28 .…”
Section: Discussionmentioning
confidence: 74%
“…Various recent reports suggest a potential role for KIR receptors in the development of CML and response to TKI treatment, although the studies included relatively small number of samples and reported contrasting findings 36–39 …”
Section: Discussionmentioning
confidence: 99%
“…35 Various recent reports suggest a potential role for KIR receptors in the development of CML and response to TKI treatment, although the studies included relatively small number of samples and reported contrasting findings. [36][37][38][39] We recruited 190 patients with chronic-phase CML treated with TKIs and KIR genes, the KLRK1 SNP (rs1049174), and KIR ligand genes HLA-A, HLA-B, HLA-C, HLA-G, HLA-F, MICA, and MICB were genotyped to characterize the effects on MR of NK receptors and their respective ligands in this population. Apart from assessing KIR gene variability, we were interested in learning more about the network of NK receptors and ligands that characterize the action of NK cells.…”
Section: Discussionmentioning
confidence: 99%